Program & faculty evaluation - Lauer, Andreas K. (Annals of Eye Science, 2017)
Graduate medical education (GME) has shifted its curricula from process-oriented approach to outcomes-oriented models. Program and faculty evaluation are methods by which educational curricula may adjust the teaching and learning environment to meet the needs and fills the gaps in GME. The measurement of educational outcomes is an essential for assessing teaching effectiveness in a shifting health care environment. In addition to trainee, program, and faculty evaluations, annual program review (APR) and evaluation and navigational changes made by the program education committee are essential to maintain effectiveness of an educational curriculum in a contemporary graduate medical training program.